Single nucleotide polymorphisms in CD40L predict endothelial complications and mortality after allogeneic stem-cell transplantation - Rachakonda, P. Sivaramakrishna; Radujković, Aleksandar; Müller-Tidow, Carsten; Kumar, Rajiv; Dreger, Peter; Luft, Thomas (Journal of oncology, 2018)
PurposeEndothelial vulnerability is a potential risk factor for complications after allogeneic stem-cell transplantation (alloSCT). The CD40/CD40 ligand (CD40L) axis contributes to inflammatory diseases and is upregulated in endothelial cells upon activation, suggesting a role in alloSCT biology. Here, we studied single nucleotide polymorphisms (SNPs) in the CD40L gene in recipients of alloSCT.Patients and MethodsThree CD40L SNPs (rs3092920, rs3092952, rs3092936) were analyzed for association with transplant-associated thrombotic microangiopathy, overall nonrelapse mortality (NRM), and NRM after acute graft-versus-host disease in 294 recipients of alloSCT without statin-based endothelial prophylaxis (SEP). The significant genotype was then put into perspective with established thrombomodulin (THBD) gene polymorphisms. Findings were validated in an independent cohort without SEP and in an additional 344 patients who received SEP.ResultsThe rs3092936 CC/CT genotype was associated with an increased risk of transplant-associated thrombotic microangiopathy (P = .001), overall NRM (P = .03), and NRM after acute graft-versus-host disease (P = .01). The rs3092936 CC/CT genotype was largely mutually exclusive of high-risk THBD SNPs. Both CD40L and THBD SNPs predicted adverse overall survival (OS) and overall NRM to a similar extent in training cohort (OS, P = .04; NRM, P < .001) and validation cohort (OS, P = .01; NRM, P = .001) without SEP. In contrast, SEP completely abolished the influence of the high-risk CD40L and THBD SNPs (P = .40).ConclusionAn increased risk of endothelial complications can be predicted before alloSCT by genetic markers in the recipient’s genome. The normalization of mortality risks in patients treated with SEP suggests a way of overcoming the negative effect of high-risk genotypes and warrants further clinical validation.